Validation of libRadtran and SBDART models under different aerosol conditions - Obregón, Maria (2016)
This study is aimed at analyzing the performance of the radiative transfer models libRadtran and SBDART for estimating the shortwave (285-2800 nm) irradiance under different aerosol conditions. For that purpose, measurements of downward irradiance at the Earth s surface in Évora and the corresponding model simulations have been compared for six selected days (03-08-2003, 15-08-2004, 24-08-2004, 18-07-2005, 19-08-2007 and 17-05-2010). The comparison between measured and simulated values shows a highly significant correlation, with determination coefficient between 0.999 and 1 for both models and slope very close to unity (between 0.992±0.004 and 1.017±0.003 for libRadtran, and between 0.997±0.004 and 1.024±0.002 for SBDART), supporting the validity of the models in the estimation of irradiance in the shortwave spectral range. Relative differences between the simulated and measured irradiances with respect to the measured values have also been calculated, being most of the differences for the six days lower than 0.2%. These small differences could be associated with experimental errors in the measurements as well as uncertainties in the input values given to the models, particularly those related with the aerosol properties. Also, relative differences between models have been calculated, obtaining values lower than 0.1%. SBDART model slightly overestimates the libRadtran simulations. The notably good agreement between simulated and measured irradiances indicates that both models can be used to estimate irradiance, provided that the models are fed with highly reliable-quality data.